2023
DOI: 10.48550/arxiv.2301.03228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graph Neural Networks for Aerodynamic Flow Reconstruction from Sparse Sensing

Abstract: Sensing the fluid flow around an arbitrary geometry entails extrapolating from the physical quantities perceived at its surface in order to reconstruct the features of the surrounding fluid. This is a challenging inverse problem, yet one that if solved could have a significant impact on many engineering applications. The exploitation of such an inverse logic has gained interest in recent years with the advent of widely available cheap but capable MEMS-based sensors. When combined with novel data-driven methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…We use an Encode-Process-Decode GNN architecture [18,19], which ensures that the dimensionality during the message-passing process is much larger than the physical parameter space, thus increasing the expressivity of the GNN. We display in Figure 1 a graphical overview of this GNN architecture.…”
Section: Architecture Of the Gnn Solutionmentioning
confidence: 99%
“…We use an Encode-Process-Decode GNN architecture [18,19], which ensures that the dimensionality during the message-passing process is much larger than the physical parameter space, thus increasing the expressivity of the GNN. We display in Figure 1 a graphical overview of this GNN architecture.…”
Section: Architecture Of the Gnn Solutionmentioning
confidence: 99%
“…Machine learning methods have emerged as data-driven general-purpose tools, that can be used for reconstructing fields from sparse sensor measurements. Numerous studies [20][21][22][23][24][25] have demonstrated the potential of neural networks to efficiently interpret and utilize sparse data in various contexts. Fully connected neural networks, as discussed in Erichson et al [20] on shallow architectures, have been successfully trained on benchmark datasets.…”
Section: Introductionmentioning
confidence: 99%
“…The layout-dependent interaction between wind turbines' aerodynamics, which lends itself to be modelled as a graph, on the one hand, and the ability of graph neural networks to effectively extrapolate [3], on the other, has led GNNs to not only become one of the hottest themes in machine learning, but also being increasingly implemented in wind energy. The vast majority of employments of GNNs in wind energy has been related with two topics: power [4,5,6] prediction tasks and wake loss [7,8,9]. Despite these numerous examples, there is yet to be presented a generalizeable and wind farm layoutagnostic GNN approach that combines predictions on wind deficit due to wake interactions, with the fatigue loads these farm-wide interactions cause.…”
Section: Introductionmentioning
confidence: 99%